“Is it banned? Is it illegal?”: Navigating Western Australia's regulatory environment for e-cigarettes - McCausland, Kahlia; Maycock, Bruce; Leaver, Tama; Wolf, Katharina; Freeman, Becky; Jancey, Jonine (Elsevier, 2021)
Background: In Australia, there is no Federal legislation that directly applies to e-cigarettes, instead, several existing laws relating to poisons, therapeutic goods and tobacco control apply. Across all Australian States and Territories, it is illegal to sell nicotine-containing e-cigarettes, however, users can legally import nicotine-containing vaporisers through the Personal Importation Scheme. Western Australia differs from other Australian States and Territories in that products which resemble tobacco products are banned, effectively prohibiting the use of e-cigarettes. This study aimed to understand how e-cigarette users navigate Western Australia's regulatory environment to access vaping products and the health and safety issues encountered.